THE METACULTURAL LOGICS OF RELIGIOUS RHETORIC IN MODERATE ISLAMIC PREACHING: A QUALITATIVE STUDY OF GUS BAHA AND GUS IQDAM - Lukman Hakim; Pardianto Pardianto (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study advances the concept of metacultural logics to explain how pesantren-based religious authority is produced, circulated, and reproduced in contemporary Islamic preaching in Indonesia. The research objects of this study are two public religious sermons delivered by Gus Baha and Gus Iqdam, prominent moderate traditionalist Muslim preachers, as circulated through offline preaching forums and digital media platforms. The article examines how rhetorical practices function not merely as persuasive strategies but as metacultural mechanisms embedded in the pesantren tradition. Employing a multi-method qualitative approach that integrates textual analysis of selected sermons and in-depth interviews with key informants, the study finds four interrelated metacultural logics shaping Gus Baha and Gus Iqdam’s religious rhetoric: intertextuality, sanad (scholarly lineage), gojlokan (light teasing), and metaphor. Intertextuality operates as an epistemic logic through which pesantren knowledge is transmitted via layered textual engagement, while sanad functions as a moral-epistemological logic that defines religious authenticity through inherited scholarly genealogy. Gojlokan and metaphor serve as pedagogical and affective logics that translate pesantren ethics into vernacular and emotionally resonant forms. Beyond preserving and renewing the pesantren moral and epistemological foundations, these metacultural logics also enable the effective circulation of religious discourse in contemporary preaching contexts.